Edukasi Bahaya Rokok Pada Anak Usia Dini di SD Lempeh Sumbawa Besar - Nur Arifatus Sholihah; Asri Reni Handayani; Kurnia Bend. Yunita Pellondou (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Smokers in Indonesia are ranked third in the world. More than 60 million Indonesians smoke. Cigarette consumption in 2008 reached 240 billion cigarettes or 658 million cigarettes per heart. This means money worth around Rp. 330 billion are